Liquidity Creation and its Impact on Economic Growth: Moderating Role of Firm Size - Asad Ali; Usman Ahamd (Audit and Accounting Review, 2023)
The study aims to examine the influence of Liquidity Creation (LC) on Pakistan's Economic Development (GDP)  to investigate the moderating role of firm size and its abiding association in this relationship. Banks create liquidity by managing their portfolios of assets and liabilities with various maturities. The current study used an estimated amount of liquidity created by commercial banks in Pakistan using the "Catfat" model over the last twenty-two years. The estimated LC is employed in this study to assess its influence on GDP growth. Additionally, the research examines the moderating role of firm size between LC and GDP. Furthermore, secondary time series data for this research was collected from the financial statements and World Bank Data from 2000-2021. The study employs a regression technique to test the hypotheses. The outcomes indicate that LC has a significant positive impact on GDP. It implies that when commercial banks create liquidity, it boosts economic growth. The results revealed that firm size does not moderate the relationship between the LC and GDP, neither strengthens nor weakens. The study put forward that conventional banks play a substantial role in contributing to Pakistan's economic growth by creating liquidity in the market. The study holds importance in its ability to shape economic policies, provide financial institutions direction, and offer investors advantages. It contributes to academic research, provides practical insights, and has worldwide applicability in enhancing comprehension of financial systems and their influence on economic growth.